Effect of opercular deformity on morphological and transcriptomic profiling of gills in golden pompano (Trachinotus ovatus) - Yuwei Wu; Qian Ma; Dihao Huang; Liuyong Wang; Qiling Zhou; Chunli Ran; Gang Chen (Aquaculture Reports)
The golden pompano (Trachinotus ovatus), one of China's most important economic fishes in marine culture, is highly susceptible to external environmental changes during early development. Skeletal deformities in the opercular complex, jaws, and vertebral column are the most common consequences. The opercular deformity can result in the exposure of the gill chamber, which may lead to adverse effects on the gill function. In this study, gill samples were collected from both sides of the unilaterally deformed golden pompano to elucidate the effect of opercular deformity on morphological characteristics and gene expression of the gills. Paraffin section, Hematoxylin-Eosin (HE) staining, and TdT-mediated dUTP nick-end labeling (TUNEL) of the gills revealed that no significant difference in morphological structure or apoptosis was identified between the gills collected from the deformed and normal sides. Transcriptome sequencing of the gill samples has detected a total of 100 differentially expressed genes (DEGs), including 66 up-regulated and 34 down-regulated genes. GO functional enrichment analysis revealed that the DEGs were significantly enriched in responses to stimulus, localization, and metal ion binding. KEGG pathway enrichment analysis of the DEGs indicated notable enrichment in pathways related to immune response and inflammation, including Staphylococcus aureus infection, leukocyte transendothelial migration, tight junction, and cell adhesion molecules pathways. These enrichment analysis results suggest that functions associated with immunity and disease, ion homeostasis, energy metabolism, and apoptosis may be influenced by the opercular deformity.